Integrating digital green management accounting with circular economy: A systematic literature review of the palm oil agroindustry - Deviarti, Holly; Nevara, Gita Addelia (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2026)
The palm oil agroindustry plays a vital role in global food supply chains but faces increasing pressure to enhance sustainability and resource efficiency. As environmental challenges intensify, integrating digital and accounting innovations has become essential for achieving circular value creation. This study conducts a systematic literature review of Scopus-indexed articles from 2019 to 2025 to examine how Digital Green Management Accounting (DGMA) supports the implementation of Circular Economy (CE) principles in the palm oil sector. The findings reveal that, although many studies address technological and environmental aspects—such as biomass utilization, waste-to-energy systems, and bio-based products—few explore the managerial accounting mechanisms that operationalize these initiatives. The review identifies a critical research gap in connecting digital accounting tools, including Material Flow Cost Accounting (MFCA) and Environmental Management Accounting (EMA), with circular performance metrics. To bridge this gap, a conceptual framework for a digital circular accounting system is proposed, integrating IoT, AI, and blockchain technologies to enhance real-time monitoring, traceability, and sustainability reporting. This framework provides strategic insights for agro-industrial firms seeking to align profitability with environmental responsibility and advance the Sustainable Development Goals (SDGs), particularly Goal 12 on responsible consumption and production.